LEFT VENTRICLE FUNCTIONAL STATUS DYNAMICS THROUGH VARIOUS ISCHEMIA CLINICAL COURSES AFTER AN ENDURED ACUTE CORONARY SYNDROME - D. A. Shvets; S. V. Povetkin (Архивъ внутренней медицины, 2017)
The aim of the research under consideration is to compare clinic instrumental parameters which characterize left ventrical functional status of the patients who have recently suffered acute coronary syndrom (ACS) and of those who endured it 24 months before within aggravated and nonaggravated ischemia clinic course. Methods and materials. The research involved 150 patients who had suffered ACS. The first group included 112 patients with non-aggravated course, the second group was represented by 38 patients with the agravated one. The methods applied were general, laboratory and instrumental. Re-examination was carried out 24 months after the suffered ACS. The global systolic and diastolic left ventrical function evaluation was perfomed with the help of echocardiograghy. The method of Tissue Doppler Imaging (TDI) was used in order to estimate segmental contractility. Results. Those patients with the aggravated ischemia clinic course are distinguished by more frequently repeated anginal atacks and by a higher functional class of blood circulation insufficiency. Comparison of the echocardiography markers within 24 months period after the suffered ACS revealed left ventrical global systolic disfunction. Considerably more patients with the aggravated clinic course have left ventrical diastolic dysfunction. The segmental contractility analysis with the help of the TDI enabled to reveal the decrease of systolic and early diastolic velocity peaks among the patients with the aggravated IHD course variant. Moreover, a lapse of basal segment longitudinal inferior wall strain value was discovered which is not compensated by the LVanteroseptal mid-segment contractility augmentation. Conclusion. As a result of the comparison of clinical instrumental parameters a global and a segmental LV dysfunctions were discovered among the patients with the aggravated IHD clinic course 24 months after an endured ACS.